STRATEGI PEMASARAN UNTUK MENINGKATKAN PENJUALAN PADA UMKM TAHU SUMEDANG BANG AMIR (Studi Kasus Pada Umkm Tahu Sumedang Bang Amir, Kecamatan Medan Denai, Kota Medan) - Nabila Iskandar; Muhammad Choir Rivaldi; Shella Gustianda; Zainarti Zainarti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to observe the marketing strategy of Tahu Sumedang Bang Amir MSMEs to increase product sales. The research method used is qualitative with a case study approach. Data was collected through in-depth interviews with MSME owners as well as direct observation of the marketing locations used. The research results showed that Tahu Sumedang Bang Amir MSMEs had not yet expanded their marketing strategy using online media and only carried out business activities at home and sold to local residents and consumers who were regular customers. However, future planning has been summarized for product and brand promotion strategies for wider marketing using online media, inter-city sales, ordering event catering and maintaining the taste that has become the taste of consumers.